Cerebrospinal Fluid Cytokine Levels After Surgery With Spinal or General Anesthesia. Issue 6 (1st November 1999) - Yeager, Mark P.; Lunt, Peter; Arruda, Janice; Whalen, Kate; Rose, Robert; DeLeo, Joyce A.
Abstract : Background and Objectives: Studies show that pain may cause neuroinflammatory changes in the spinal cord. These inflammatory changes could be caused by circulating factors such as plasma cytokines or could be a primary neuroimmune response of the central nervous system following peripheral nerve injury. To identify the possible effects of peripheral trauma and pain on the cytokine environment of the spinal cord, interleukin-6 (IL-6) and interleukin-10 (IL-10) concentrations in plasma and cerebro-spinal fluid (CSF) were measured before and after hip replacement surgery. Methods: The investigation used a prospective, observational design to measure cytokine levels in samples of plasma and CSF by enzyme-linked immunosorbent assay (ELISA). Samples were taken from surgical patients before and after surgery under general anesthesia or spinal anesthesia performed with or without a spinal catheter. Reference samples were also obtained from healthy control subjects. Results: Both plasma and CSF levels of IL-6 increased substantially after major surgery with either general or spinal anesthesia. No significant correlation was observed between plasma IL-6 and CSF IL-6 levels, suggesting a central origin for increased CSF cytokine levels. IL-10 did not change in plasma or CSF after surgery. Plasma and CSF IL-6 and IL-10 cytokine levels were very low or undetectable in healthy controls. Conclusions: Major orthopedic surgery leads to elevated CSF levels of the proinflammatory cytokine, IL-6. The origin of increased CSF IL-6 may be central because there was no significant correlation with plasma levels.